MODELO DE REGRESSÃO LINEAR NA INTERPRETAÇÃO DOS EFEITOS DAS FONTES DE ADUBAÇÃO NITROGENADA EM TRIGO MULTICOLMO - Battisti, Gabriel K.; Wentz, Renan; Boff, Jose T.; Oliveira, Juliana; Arenhardit, Emilio; Schiavo, Jordana; Matter, Edegar; Ghaviragui, Juliano; Maixner, Adriano R.; Silva, Jose A. G. d. (Salão do Conhecimento, 2013)
Resumo